A new deterministic approach for transmission system planning in deregulated electricity markets. (December 2015) - Capasso, A.; Cervone, A.; Lamedica, R.; Palagi, L.
Highlights: A new methodology for transmission systems planning in deregulated electricity market is proposed. The concept of criticality in transmission systems is proposed and an appropriate index is defined. The methodology is based on the resolution of different optimization problems. An application of the proposed methodology has been made on a 24 bus test grid. Abstract: The transmission expansion planning has to guarantee the increase of competitiveness of market participants ensuring high standards of reliability and the safety of system operation. The congestion occurrences limit the competitiveness and cause an increase of costs for the final users. In the present paper a new deterministic methodology is proposed in order to support the static transmission system planning in deregulated electricity markets, which are characterized by high levels of uncertainties. The concept of criticality in transmission system planning is introduced: congestion cases and bottlenecks represent critical cases of the transmission system from a point of view of planners. The proposed approach allows individuating these critical states by solving specific optimization problems and performing reliability analyses based on the N − 1 criterion. A comparison of different transmission expansion plans is performed assessing the indices of criticality, whose evaluation is based on measuring the exploitation of the margin capabilities of transmission lines. The indices have been used to measure the reduction of criticality associated to expansion plans. The proposed approaches have been applied on two different test systems in order to demonstrate the effectiveness of the methodology in transmission system planning applications.